Assessment of Sexual Dimorphism from the Mastoid Triangle Using 3d CT scan in Nepalese Population - Singh, Pankaj Kumar; Karki, Raj Kumar; Khan, Abdul Sami; Shah, Dhiraj Kumar; Bhardwaj, Sushant (Birat Journal of Health Sciences, 2021)
Introduction: Skull plays an important role, second only next to pelvis for sex determination. In skull, mastoid and occipital region due to its anatomical location is the most protected region, offering high resistance to decomposition and any form of tempering. With the intension of studying sexual dimorphism in the mastoid region involving mastoid process, we initiated this study. The technique we adopted was first introduced by Paiva and Segre, i.e. measuring the distance between three cranio-metric land mark (Porion, Mastoidale, and Asterion) and calculating the area of the triangle to study sexual dimorphism. Objective: The objective of this study is to determine sex based on mastoid triangle dimensions measured in 3D reconstructed computed tomography of the skull. Methodology: The study included 196, 3D reconstructed CT scan images of skull, 98 of which were males and 98 of which were females. The three craniometric points were marked to demarcate the mastoid triangle on both side (mention the software used).Heron’s formula was used for measurement of mastoid triangle areas. Result: Descriptive statistics and the student t-test revealed that males have larger mastoid triangle dimensions in all measurements than females, with a significant difference (p<0.000) between them. The paired t-test revealed no statistically significant difference (p<0.05) between the right and left sides. Apart from angle asterion (p<0.05) on the right side, no other mastoid triangle angles on either side showed a significant difference. The predictability of mastoid triangle measurements and areas was determined using a discriminant function and ROC curve analysis. The calculated mastoid triangle measurements and areas were 72.5 % of Asterion to Porion, 74.5 % of Asterion to Mastoidale, 86.3 % of Mastoidale to Porion, and 88.2 % of areas, respectively. Conclusion: The study findings suggest that mastoid triangle could be used to determine gender in the case of fragmentary skull remains by the forensic experts in the course of investigation. In order to generalize the data nationally, an autopsy-based, large sample size study on different age groups should be conducted.